2021
DOI: 10.1111/tpj.15484
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a GC‐MS‐based 13C‐positional isotopomer approach suitable for investigating metabolic fluxes in plant primary metabolism

Abstract: 13 C-Metabolic flux analysis ( 13 C-MFA) has greatly contributed to our understanding of plant metabolic regulation. However, the generation of detailed in vivo flux maps remains a major challenge. Flux investigations based on nuclear magnetic resonance have resolved small networks with high accuracy. Mass spectrometry (MS) approaches have broader potential, but have hitherto been limited in their power to deduce flux information due to lack of atomic level position information. Herein we established a gas chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 107 publications
(158 reference statements)
3
29
0
Order By: Relevance
“…That said, cytosolic MDH4 and especially PEPc were highly abundant in Arabidopsis GCs and present in larger amounts compared to MCs (Fig. 5h ), in agreement with the overall idea that anaplerotic CO 2 fixation is the main pathway of carbon assimilation in GCs 17 , 50 , 52 , 57 , 66 . For example, early 14 C-labelling experiments showed that CO 2 was fixed into Mal 2– at high rates both in the dark and the light in GCs, whereas in MCs, 14 C was enriched in 3-PGA and sucrose in the light and Mal 2– only in the dark 50 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…That said, cytosolic MDH4 and especially PEPc were highly abundant in Arabidopsis GCs and present in larger amounts compared to MCs (Fig. 5h ), in agreement with the overall idea that anaplerotic CO 2 fixation is the main pathway of carbon assimilation in GCs 17 , 50 , 52 , 57 , 66 . For example, early 14 C-labelling experiments showed that CO 2 was fixed into Mal 2– at high rates both in the dark and the light in GCs, whereas in MCs, 14 C was enriched in 3-PGA and sucrose in the light and Mal 2– only in the dark 50 .…”
Section: Discussionsupporting
confidence: 84%
“…For example, early 14 C-labelling experiments showed that CO 2 was fixed into Mal 2– at high rates both in the dark and the light in GCs, whereas in MCs, 14 C was enriched in 3-PGA and sucrose in the light and Mal 2– only in the dark 50 . Furthermore, recent 13 C-feeding experiments demonstrated a faster 13 C enrichment in Mal 2– in isolated epidermal fragments compared with the whole rosette of Arabidopsis 17 , 52 , 67 . Fixation of CO 2 via PEP carboxylation ultimately leads to the formation of Mal 2– , further highlighting the central role of this metabolite for GCs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such discrepancies are, however, best explained by the different subcellular localization of both TRXs and the specific enzyme targets of TRX o1 such as SDH and fumarase (Daloso et al, 2015; Hou et al, 2021). The direct impact on both enzymes was discussed to support the regulation of the different flux modes of the TCA-cycle and its inactivation in the light in addition to PDH regulation (Sweetlove et al, 2010; Araújo et al, 2011; Daloso et al, 2015; Lima et al, 2021). Interestingly, the latter statement is further supported by our metabolite analysis since pyruvate significantly accumulates in both TRX single mutants on a short-term (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since their inception, isotopic labeling experiments (ILEs) have been applied for various purposes, such as pathway elucidation, model validation, and determination of intracellular flux rates in a host of organisms from bacteria [ 1 ] to eukaryotes [ 2 , 3 ], plants [ 4 6 ] and mammalian cell lines [ 7 , 8 ]. Thus, they have contributed significantly to strain characterization, screening and rational strain development.…”
Section: Introductionmentioning
confidence: 99%